تاثير تدریبات وفق اسلوب الفارتلك في بعض المتغيرات الوظيفية والبدنية لدى لاعبات نادي جوارقورنة بكرة القدم الصالات - الله, أ. م. د. هانا جلال فتح (Sulaimani Journal for Humanities, 2023)
The study aims to identify the effect of training according to the fartlek method on a number of physiological abilities and physical effort for female futsal players aged (16-20) years. The researcher used the experimental method to suit the nature of the study., as fartlek exercises were prepared at a rate of (2 training units) per week for a period of time. (9 weeks) and physical tests were conducted, the speed test (30-meter sprint), and the 450-meter sprint test (measuring speed endurance), physiological tests, and after statistical treatments, the researcher concluded that the exercises specific to the fartlek training method had an effect on all the tests under study, with statistical significance in the pre- and post-tests. In favor of the post-test, the researcher found that there were significant differences in the post-tests among the research sample. The researcher concluded a noticeable improvement in the physiological research variables (heart rate after effort and respiratory rate after effort) and the results showed statistically significant differences between the pre- and post-tests and in favor of the post-measurement. And a noticeable improvement in the physical research variables (speed endurance and transitional speed) as a result of regularity in fartlek training
Keywords: The effect of fartlek training; Functional variables; physical; futsal